Innate Immune Responses to Wildtype and Attenuated Sheeppox Virus Mediated Through RIG-1 Sensing in PBMC In-Vitro - Chibssa, Tesfaye Rufael; Kangethe, Richard Thiga; Berguido, Francisco J.; Settypalli, Tirumala Bharani K.; Liu, Yang; Grabherr, Reingard; Loitsch, Angelika; Sassu, Elena Lucia; Pichler, Rudolf; Cattoli, Giovanni; Diallo, Adama; Wijewardana, Viskam; et al. (Frontiers in Immunology, 2021)
Sheeppox (SPP) is a highly contagious disease of small ruminants caused by Sheeppox virus (SPPV) and predominantly occurs in Asia and Africa with significant economic losses. SPPV is genetically and immunologically closely related to goatpox virus (GTPV) and lumpy skin disease virus (LSDV), which infect goats and cattle. SPPV live attenuated vaccines (LAVs) are used for vaccination against SPP and Goatpox (GTP). Mechanisms related to innate immunity elicited by SPPV are unknown. Although adaptive immunity is responsible for long-term immunity, it is the innate responses that prevent viral invasion and replication before LAVs generate specific long-term protection. We analyzed the relative expression of thirteen selected genes that included pattern recognition receptors (PRRs), Nuclear factor-κβ p65 (NF-κβ), and cytokines to better understand the interaction between SPPV and its host. The transcripts of targeted genes in sheep PBMCs incubated with either wild type (WT) or LAV SPPV were analyzed using quantitative PCR. Among PRRs, we observed a significantly higher expression of RIG-1 in PBMC incubated with both WT and LAV, with the former producing the highest expression level. However, there was high inter-individual variability in cytokine transcripts levels among different donors, with the expression of TNFα, IL-15, and IL-10 all significantly higher in both PBMC infected with either WT or LAV as compared to control PBMC. Correlation studies revealed a strong significant correlation between RIG-1 and IL-10, between TLR4, TNFα, and NF-κβ, between IL-18 and IL-15, and between NF-κβ and IL-10. There was also a significant negative correlation between RIG-1 and IFNγ, between TLR3 and IL-1 β, and between TLR4 and IL-15 (P< 0.05). This study identified RIG-1 as an important PRR in the signaling pathway of innate immune activation during SPPV infection, possibly through intermediate viral dsRNA. The role of immunomodulatory molecules produced by SPPV capable of inhibiting downstream signaling activation following RIG-1 upregulation is discussed. These findings advance our knowledge of the induction of immune responses by SPVV and will help develop safer and more potent vaccines against SPP and GTP.